Gathering the sun : an alphabet in Spanish and English - Ada, Alma Flor.; Zubizarreta, Rosa (Rosalma); Silva, Simon ([New York] : HarperCollins, 1997)
A book of poems about working in the fields and nature s bounty, one for each letter of the Spanish alphabet.
Keywords: Children s poetry, Hispanic American (Spanish); Spanish language -- Alphabet; Agricultural laborers -- Juvenile poetry; Hispanic American poetry (Spanish); Alphabet; Agricultural laborers -- Poetry; Spanish language materials -- Bilingual